A geometric description of the spatial coherence and Babinet´sp like principle for the fringe visibility - Rabal, Héctor Jorge (2015)
The concept of spatial coherence is usually hard to comprehend the first time that it is studied. We propose here a fully intuitive geometric description that does not contain mathematical difficulties, and permits one to understand how a Young’s fringe stationary system is obtained with a source not spatially coherent. It is based in a very simple experiment that permits the detection of spatial coherence in a scene. Experimental results are shown. Using this approach, a Babinet-‐like principle for the visibility of the Young’s fringes is proposed and experimentally demonstrated.